2017
DOI: 10.5812/hepatmon.43500
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Common Variations of ABCB4, ATP8B1 and ABCB11 Genes in Patients with Progressive Familial Intrahepatic Cholestasis

Abstract: Background: Progressive familial intrahepatic cholestasis (PFIC) is a heterogeneous group of hepatic disorders that can progress rapidly, leading to cirrhosis and death due to liver failure. Mutations and variations in three genes, including ATP8B1, ABCB11, and ABCB4, have been reported to be the main genetic cause of three subtypes of this disorder including PFIC1, PFIC2, and PFIC3, respectively. Objectives: Therefore, the aim of this study was to investigate more common mutations and variations associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…However, to date, no studies have been performed to evaluate the role of this variant in the susceptibility to BA. Publications have been done in patients with cholestasis, especially in PFIC [19–21] …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, to date, no studies have been performed to evaluate the role of this variant in the susceptibility to BA. Publications have been done in patients with cholestasis, especially in PFIC [19–21] …”
Section: Discussionmentioning
confidence: 99%
“…Publications have been done in patients with cholestasis, especially in PFIC. [19][20][21] In this study, we selected the patients who were confirmed with BA by Kasai surgery and liver biopsy for genotype analysis. We performed whole exome sequencing of several patients with BA to identify the variants that might be the cause of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation